Displacement of Aphytis chrysomphali by Aphytis melinus, parasitoids of the California red scale, in the Iberian Peninsula - Boyero, Juan Ramon; Vela, Jose Miguel; Wong, Eva; Garcia Ripoll, Carlos; Verdú, Maria Jesús; Urbaneja, Alberto; Vanaclocha, Pilar (Spanish Journal of Agricultural Research, 2014)
Parasitoids are the main natural enemies of the California red scale, Aonidiella aurantii (Maskell) and on occasion can regulate their populations. To increase their effectiveness, inoculative or augmentative releases of parasitoids are promoted. Previous to the implementation of any release strategy an important and necessary step is to acquire knowledge on the parasitoid fauna associated with this key phytophagous pest. Parasitoids were surveyed and quantified in Spanish citrus orchards between 2005 and 2009. Aphytis melinus DeBach (87.1%) resulted as the dominant species, followed by Aphytis chrysomphali (Mercet) (15.9%), Encarsia perniciosi (Tower) (2.4%) and Aphycus hederaceus (Westwood) (0.004%). Overall, higher levels of parasitism were recorded in fruit than in twigs. Scales in fruit were parasitized at similar levels by the different parasitoid species whereas E. perniciosi was more active in twigs. Data eventually reveal the recent displacement of A. chrysomphali by A. melinus. The implications of these results on the biological control of A. aurantii are discussed and this information will be useful in the decision of IPM strategies for this pest.